The prevalence of postpartum depression and its consequences in women in Brazil (Research, Society and Development, 2021)
Objective: To assess the prevalence and associated factors for the onset of depression in pregnant women in the postpartum period. Methods: a critical review of publications in Scielo, Lilacs and Google Scholar, referring to the years 2010 to 2021, was performed, using terms and descriptors related to postpartum depression. Articles that did not meet the inclusion criteria, those that presented duplicate data and articles that, after detailed reading, did not meet the objective proposed in this review were excluded. Results: in these studies that used women during pregnancy, immediate and late postpartum periods, with or without reproductive history, it was related that PPD is a condition that must be treated as soon as possible so that there is a good family relationship, physical health and of the child. Conclusion: PPD is a highly prevalent disorder that can compromise the quality of the relationship between mother and child. There are numerous factors that contribute to this event, such as irritability, feeling of helplessness and hopelessness, the feeling of being unable to deal with new situations, depends on a series of factors, which does not allow the realization of a prognosis based on isolated factors.